(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2012)
The present study aims to conduct a survey in the Administration and Behavior Analysis major national journals, to identify categories pertaining to organizational culture and to provide a behavior analysis understanding of organizational culture. We conducted a survey between the years 1997 and 2008, in journals of Management and Psychology. The procedure for performing this literature review initially involved access to a database of journals volumes searching for summaries. All articles abstracts and separate works that addressed issues related to the conceptual universe of organizational culture, regardless of the approach, were read. Finally, articles about the subject organizational culture were read and categorized. It was noted that, in the behavioral tendency, the organizational culture can be analyzed in terms of three components: Important results for survival, practices of organizational members and connections between results and practices. With this, we identified that the study of cultural practices or cultural processes have been relevant to the field of Organizational Behavior. Moreover, the issue is also of fundamental importance to enlarge the consolidation of behavior analysis as a science, and is a producer of basic and applied knowledge and as a technological area responsible for behavioral changes.